IMPLEMENTASI NILAI GURU PAI DALAM AMANAT UPACARA BENDERA UNTUK PEMBENTUKAN KARAKTER ISLAMI SISWA SALAFIYAH ULA ICBB YOGYAKARTA - Sakinah, Nabila Aulia; Masitoh, Anita Dewi; Izzah, Siti Ulfiatul; Wardani, Widyaningtyas Kusuma (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe the implementation of Islamic Religious Education (PAI) values in teachers’ guidance addresses during flag ceremonies as a medium for shaping students’ Islamic character at Salafiyah Ula Islamic Center Bin Baz (ICBB) Yogyakarta. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving three main informants: Ika Sari Wantika, Lestari Pujiastuti, and Hanifah. The results show that the flag ceremony at Salafiyah Ula ICBB is routinely held every Monday morning with a structured and disciplined arrangement of activities. The teachers’ guidance speeches play an essential role in internalizing Islamic values such as discipline, responsibility, gratitude, honesty, and respect toward parents and teachers. The ceremony management is well-organized through theme planning, task distribution, and exemplary teacher behavior, which positively impacts students’ spirituality. Students demonstrate improvements in discipline, moral conduct, and habits of prayer and gratitude. Based on interviews, the teachers’ guidance speeches significantly influence the formation of students’ Islamic character, especially when followed by daily habituation activities. These findings align with Fathoni (2021), who emphasized that integrating Islamic education values into school routines helps build students’ religious and disciplined character.